2001
DOI: 10.1164/ajrccm.163.2.2006158
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Genes for Rapid Decline of Lung Function in the Lung Health Study

Abstract: The genes that contribute to the genetic susceptibility to chronic obstructive pulmonary disease (COPD) remain largely unknown. We hypothesized that widely divergent rates of decline in lung function in smokers would be a robust phenotype for detection of genes that contribute to COPD severity. We selected 283 rapid decliners (deltaFEV1 = -154 +/- 3 ml/yr) and 308 nondecliners (deltaFEV1 = +15 +/- 2 ml/yr) from among smokers followed for 5 yr in the NHLBI Lung Health Study. Rapid decline of FEV1 was associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
148
0
12

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(174 citation statements)
references
References 22 publications
14
148
0
12
Order By: Relevance
“…A more interesting parallel can be drawn with a re- cent study indicating an effect of low-activity mEH alleles and the rapid decline of lung function in patients with emphysema. 28 Analogously to our results, in fact, differences were evidenced in the long-term outcome and the timing of disease evolution, as would be expected for the effect of a modifier trait of chronic tissue damage in diseases characterized by prolonged courses, variable clinical expression, and multiple causes. The comparison between cirrhotic patients with or without HCC indicated that mEH low-activity alleles exerted an independent effect on the risk of cancer, although this was essentially restricted to men.…”
Section: Discussionsupporting
confidence: 87%
“…A more interesting parallel can be drawn with a re- cent study indicating an effect of low-activity mEH alleles and the rapid decline of lung function in patients with emphysema. 28 Analogously to our results, in fact, differences were evidenced in the long-term outcome and the timing of disease evolution, as would be expected for the effect of a modifier trait of chronic tissue damage in diseases characterized by prolonged courses, variable clinical expression, and multiple causes. The comparison between cirrhotic patients with or without HCC indicated that mEH low-activity alleles exerted an independent effect on the risk of cancer, although this was essentially restricted to men.…”
Section: Discussionsupporting
confidence: 87%
“…(1) Even a slight decrease in AAT levels, such as that observed in individuals with the MZ genotype, can increase the risk of developing pulmonary diseases, (13) and the impaired function of AAT denatured by oxidation in smokers (even in those presenting normal AAT levels) can contribute to the development of lung injury. (5) These facts seem to indicate that AAT availability is extremely important for the protection of the lung and, probably, for the maintenance of the adequate state of many other organs and systems.…”
Section: Resultsmentioning
confidence: 99%
“…Sandford and his colleagues have taken advantage of the well-characterized Lung Health Study cohort study to examine gene variants associated with rapid decline in lung function (1). They selected the phenotypic extremes from among the approximately 6,000 individuals in that study; the approximately 300 continued smokers who had the most rapid and the approximately 300 who had the least rapid decline in FEV 1 over the first 5 years of the study.…”
Section: Candidate Gene Studiesmentioning
confidence: 99%